Progress on PD-1/PD-L1 Checkpoint Inhibitors in Lung Cancer - Di ZHANG; Jiaqi HUANG; Chufeng ZHANG; Yan GUAN; Qisen GUO (Chinese Journal of Lung Cancer, 2019)
In recent years, research on immunotherapy has made great progress. Currently, immunotherapy has made significant breakthrough, especially programmed death 1/programmed death-ligand 1 (PD-1/PD-L1) checkpoint inhibitors (e.g, Nivolumab, Pembrolizumab, Atezolizumab, Durvalumab and Avelumab, etc.) have brought clinical benefits to patients with various pathological types of lung cancer, including squamous cell carcinoma, adenocarcinoma and small cell lung cancer. In this paper, the application value and current status of PD-1/PD-L1 checkpoint inhibitors in lung cancer were comprehensively analyzed by reviewing and interpreting representative clinical studies. Based on the results of various large-scale clinical trials results, the indications of immunotherapy in lung cancer have been continuously broadened, and the details of immunotherapy have also been constantly optimized. However, immunotherapy still faces many challenges, such as the selection of immune combination strategies, the exploration of biomarkers, the management of adverse events, the feasibility of application of driver gene mutation population and so on. In this article, we made a systematic review about the latest progress of PD-1/PD-L1 checkpoint inhibitors in lung cancer, in order to provide cutting-edge reference for the clinical workers.